Socialisation of Implementation of Bawaslu Regulations and Non- Regulations in Baubau City: English - Zubair, Zubair; Eko Satria; Mashendra; Samsul; Yayan Serah (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The socialisation of election supervision regulations is crucial for maintaining transparency and integrity in the electoral process. It ensures stakeholders, including organizers, participants, observers, and voters, understand the rights, obligations, and procedures, leading to increased legal compliance and a fair process. Effective socialisation can also reduce conflicts and disputes, fostering public trust in the election supervisor's integrity. Activities were conducted to increase understanding of Bawaslu regulations and non-regulations during the 2024 General Election. In collaboration with Bawaslu Baubau City, participants included Sub-District Supervisory Committees and Election Monitors. Understanding rules promotes equality, fairness, and social stability by preventing abuse and utilizing legal loopholes. It also allows for organized and productive interactions, preventing conflicts and chaos. Prioritizing rules is crucial for individuals and organizations to make informed decisions, maintain equality, and preserve social stability. Conclusion in this article, Understanding regulations is essential for societal stability, justice, and order. It provides a transparent framework for interactions, promoting equality and fairness. It prevents conflicts and disorder, ensuring a more organized society. Election organizers must have a thorough understanding of electoral law to perform their duties professionally and maintain integrity. This knowledge strengthens the capacity of electoral management authorities and creates democratic elections with integrity.